2010
DOI: 10.1371/journal.pone.0014129
|View full text |Cite
|
Sign up to set email alerts
|

Spike Avalanches Exhibit Universal Dynamics across the Sleep-Wake Cycle

Abstract: BackgroundScale-invariant neuronal avalanches have been observed in cell cultures and slices as well as anesthetized and awake brains, suggesting that the brain operates near criticality, i.e. within a narrow margin between avalanche propagation and extinction. In theory, criticality provides many desirable features for the behaving brain, optimizing computational capabilities, information transmission, sensitivity to sensory stimuli and size of memory repertoires. However, a thorough characterization of neuro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

42
276
7
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 196 publications
(328 citation statements)
references
References 76 publications
(140 reference statements)
42
276
7
3
Order By: Relevance
“…Neuronal avalanches describe the spatiotemporal organization of synchronized activity in superficial layers of cortex. They have been demonstrated in spontaneous activity in vitro (Beggs and Plenz, 2003;Plenz, 2006, 2008) and in ongoing activity in vivo (Gireesh and Plenz, 2008;Petermann et al, 2009;Hahn et al, 2010;Ribeiro et al, 2010). Importantly, avalanche size, s, distributes according to a power law, P(s) ϳ s ␣ with exponent ␣ close to Ϫ1.5, a hallmark of critical state dynamics (Plenz and Thiagarajan, 2007;Klaus et al, 2011).…”
Section: Higher-order Interactions Are Essential For Neuronal Avalancmentioning
confidence: 99%
“…Neuronal avalanches describe the spatiotemporal organization of synchronized activity in superficial layers of cortex. They have been demonstrated in spontaneous activity in vitro (Beggs and Plenz, 2003;Plenz, 2006, 2008) and in ongoing activity in vivo (Gireesh and Plenz, 2008;Petermann et al, 2009;Hahn et al, 2010;Ribeiro et al, 2010). Importantly, avalanche size, s, distributes according to a power law, P(s) ϳ s ␣ with exponent ␣ close to Ϫ1.5, a hallmark of critical state dynamics (Plenz and Thiagarajan, 2007;Klaus et al, 2011).…”
Section: Higher-order Interactions Are Essential For Neuronal Avalancmentioning
confidence: 99%
“…We study Bak-TangWiesenfeld sandpile dynamics (23,24) on networks derived from real, interdependent power grids and on sparsely coupled, random regular graphs that approximate the real topologies. Sandpile dynamics are paradigms for the cascades of load, self-organized criticality, and power law distributions of event sizes that pervade disciplines, from neuronal avalanches (25)(26)(27) to cascades among banks (28) to earthquakes (29), landslides (30), forest fires (31,32), solar flares (33,34), and electrical blackouts (15). Sandpile cascades have been extensively studied on isolated networks (35)(36)(37)(38)(39)(40)(41).…”
mentioning
confidence: 99%
“…In particular, the observation of neuronal avalanches motivated the search for computational models presenting this phenomenon [8][9][10][11][12][13]. The key interest in these simulations is to find what are the conditions for the occurrence of power laws in the size and duration distributions of avalanches.…”
mentioning
confidence: 99%
“…Moreover, some authors showed that the critical state may optimize the dynamical (input) range [9,14], the memory and learning processes [10], and the computational power of the brain [5][6][7]. However, up to now, the computational models rely on very simplified neuron models like branching processes [8], cellular automata [9,13] or integrate-and-fire neurons [12].…”
mentioning
confidence: 99%